Facile One‐Pot Conversion of Petroleum Asphaltene to High Quality Green Fluorescent Graphene Quantum Dots and Their Application in Cell Imaging. (1st June 2016) - Zhao, Pinhui; Yang, Menglong; Fan, Weiyu; Wang, Xiaojuan; Tang, Fanlong; Yang, Chunpeng; Dou, Xiaowei; Li, Suying; Wang, Yanan; Cao, Yanwei
Abstract : Benefiting from the natural nano‐size graphene‐structure in natural asphaltene material, a facile one‐pot route, mild chemical oxidation of low‐value petroleum asphaltene followed by routine ammonium neutralization, is presented to produce high quality graphene quantum dots (GQDs). The asphaltene‐derived GQDs possess a variety of oxygen‐containing and nitrogen‐containing functional groups such as carboxyl, hydroxyl, amine, and nitro groups. They present such excellent fluorescence properties as stable ability to retain strong green fluorescence within a relative broad excitation range in a bio‐suitable pH range of 4–7, high photoluminescence quantum yield of 18% and good fluorescent stability against photobleaching. And they are much smaller and thinner than most reported GQDs, displaying good biocompatibility with low cytotoxicity, effective cellular uptake, and excellent fluorescent probe performance for cancer cell imaging. Abstract : From natural asphaltene to high quality Graphene Quantum Dots (GQDs): Benefiting from the natural nano‐size graphene‐structure in raw asphaltene material, a facile cheap route, one‐step chemical oxidation of asphaltenes, is presented to produce high quality GQDs. The asphaltene‐derived GQDs are much smaller and thinner than most reported GQDs, with excellent properties of excitation‐tuned green fluorescence and biocompatibility.